Sustainable development, e-learning and Web 3.0: A descriptive literature review - Mohamed Sofiadin, Aidrina Binti (Emerald Group Publishing Ltd, 2014)
Purpose – The purpose of this paper is to present a descriptive literature review and a classification scheme for studies on sustainable development, e-learning and Web 3.0 that contribute toward sustainable e-learning. The aims are to discover and highlight some ideas on developing a sustainable learning in higher education in Malaysia. Design/methodology/approach – The paper examines the elements of e-learning, technology, application, sustainable development and teaching and learning principles that contribute toward a sustainable e-learning through a descriptive literature review approach and a classification scheme. Findings – The findings show that even though sustainable e-learning research is still limited, contributions to sustainable e-learning were recognized and some ideas and perspectives for the development of a sustainable e-learning framework were identified. Furthermore, this paper identified the gaps in the findings; therefore, this paper will try to minimize these gaps through the initial sustainable e-learning framework. Originality/value – The paper is expected to provide further ideas of developing a sustainable e-learning framework, as well as the importance of a sustainable e-learning to provide quality learning through technology, application, sustainable development and teaching and learning principles perspectives.